Recent evidence comparing combination of conventional synthetic disease-modifying antirheumatic drugs with biologic disease-modifying antirheumatic drugs in rheumatoid arthritis - Abhishek Zanwar; Sakir Ahmed; Durga Prasanna Misra; Vikas Agarwal; Aman Sharma; Anupam Wakhlu; Vir Singh Negi (Indian Journal of Rheumatology)
Rheumatoid arthritis (RA) is a chronic, disabling inflammatory arthritis often treated with a variety of disease-modifying antirheumatic drugs (DMARDs), whether conventional synthetic DMARDs (csDMARDs), targeted synthetic DMARDs (tsDMARDs), or biological DMARDs (bDMARDs). Most patients with RA are seropositive, have significant disease activity at presentation to the Rheumatologist and may have erosions at the time of diagnosis, all of which are poor prognostic factors. Patients with RA are often initially started on methotrexate (MTX), with addition of other DMARDs, the usual practice in the event of failure of/suboptimal response to MTX monotherapy. Since the recent guidelines by the European League against Rheumatism favor the use of bDMARDs over the combination of csDMARDs following the failure of MTX monotherapy in patients with such poor prognostic factors, we decided to review the recent literature comparing combination csDMARDs with bDMARDs. Long-term follow-up of landmark trials such as the Behandel-Strategieëen study (10 years) and NEO-RACo study (5 years) as well as other trials supports similar efficacy of both strategies in terms of clinical and functional outcomes. Whereas some studies have shown a minor but statistically significant progression of radiographic damage in those receiving combination of csDMARDs versus those on bDMARDs, others have not, further confirmed in a recent meta-analysis. Thus, keeping in mind, the similar efficacy and better cost-effectiveness of combination of csDMARDs, this should be the preferred strategy following failure of MTX monotherapy. bDMARDs should be reserved when combination csDMARDs fail, especially in an Indian scenario where most patients are poor and a majority of healthcare is not government-sponsored.